SELECTED PLANT PATHOGENIC FUNGAL CULTURE FILTRATES (SECONDARY METABOLITES) AS POTENTIAL BIO-HERBICIDES - Ovini, I.R.; Pushpanji, K.; Pakeerathan, K.; Mikunthan, G. (9 TH YSF SYMPOSIUM,National Science and Technology Commission, 2020)
Introduction A weed is considered unwanted plant in a particular situation when it grows in a wrong place. Weeds remain problematic to agriculture, forestry, rural and urban landscaping, transport especially motorways and railway tracks, and fresh water ecosystem except their use in indigenous medicine as medicinal herbs. Weeds can be controlled by manually, mechanically, biologically and chemically. The discovery and introduction of the phenoxyacetic herbicides laid a novel era in the field of agricultural weed control. World consumption of herbicides is 44 % [1]. Herbicides are synthetic chemicals that cause many health issues to human, wild and farm animals. Moreover, application of such toxic chemicals not only may affect ecosystem functions such as productivity and food web interactions, and thus the services aquatic ecosystems provide [2], but also may cause unintentional injury to crop and other non-target vegetation and other organisms in an area by faulty application techniques. Consumers are not willing to by herbicides applied fruits and vegetables. Herbicide usage has resulted in plant evolution and adaptation by the selection of genetic traits conferring phenotypic resistance and allowing weedy plants to survive and reproduce in the presence of herbicides. Weeds have evolved resistance to 23 of the 26 known herbicide sites of action and to 163 different herbicides. Due to the hazardous nature of herbicides (Glyphosate, Atrazine, Metam and etc.), many herbicides have been banned in worldwide. The complexity of these situations has resulted in a need to develop a holistic sustainable eco-friendly weed management programme throughout the farming period. Ecofriendly secondary metabolites like ethylene-inducing peptide 1–like (NLP) proteins from microbes are now being targeted to produce novel herbicides and several successful findings have been reported in recent literatures. Phytophthora infestans is the causal agent for late blight in potato and P. infestans producing NLPs and their mode of action have been identified [3]. Botrytis cinerea is also one of the Ascomycete fungi causing disease on crops called gray mold. Botrytis cinerea produces a range of cell-wall-degrading enzymes, toxins and other low-molecular-weight compounds such as oxalic acid [4]. Fusarium solani is implicated in plant disease as well as human disease. This species can decompose cellulose at an optimal pH of 6.5 and temperature of 30°C. Culture filtrates of Fusarium solani can be used to control weeds [5]. According to above information, this investigation was planned to study the potential of using the microbial toxins of Phytophthora infestans, Fusarium solani and Botrytis cinerea as an effective bio herbicide to control weeds.